(untitled) (Quinto Sol, 2013)
Within the Law, it is posible make a difference between subjective rights (individual´s faculty) and objective rights (society´s order). The Law is not exclusively one or the other; but rather an order which connects both parts. This mechanism shows difficulties because the movement makes them part of a complex and delicate system. This paper attempts to observe this mechanism working; to understand the construction of this order as part of the new needs of certain groups and see how they take shape giving birth to a new conception of family and inheritance during the first half of 19th century.